Techno-Economic Analysis of Glycerol Valorization via Catalytic Applications of Sulphonic Acid-Functionalized Copolymer Beads - Al-Saadi, Luma Sh.; Eze, Valentine C.; Harvey, Adam P. (Frontiers in Chemistry, 2020)
Design of experiment (DoE), response surface analysis was employed for the first time to study effect of DVB (20 -80 wt. %), diluent (0-100 wt. %) and mixing (200-900 rpm) were tested on the beads’ physical properties and on swelling ability. The highest beads performances, in terms of mechanical stability, surface area, swelling ability was sulphated and tested in converting of glycerol to a valuable product “solketal”. Process options for glycerol valorisation to solketal using synthesised sulphonic acid-functionalised styrene-divinylbenzene (ST-DVB-SO3H) copolymer beads and techno-economic analysis of the processes have been investigated. 3 processes were evaluated: a 2 one-stage processes at 8.5 wt. % catalyst, and 50 °C, based on either 6:1 acetone to glycerol molar ratio (87% conversion) or 12:1 (98% glycerol to solketal conversion) and a 2-stage route (2 acetone additions), where ≥ 98% conversion can be achieved with lower overall acetone use (10:1 acetone to glycerol molar ratio and 50 °C). Techno-economic analyses of the three solketal options were performed using Aspen (HYSYS), based on a fixed capacity of 100,000 te/y and 20 years lifetime. The techno-economic analyses showed that the net present values (NPV) for the solketal process options were $707M for the two-stage, $384M for the one-stage at 6:1 acetone to glycerol molar ratio, and $703M for one-stage at 12:1 acetone to glycerol molar ratio. The break-even prices for these solketal processes were $2058/ ton for the one-stage at 12:1 of acetone and two-stage and $2088/ton for the one-stage at 6:1 of acetone, which is lower than current price of solketal $3000 /ton. The two-stage process found to be the most effective method of glycerol valorisation production to solketal.